1996
DOI: 10.1097/00007632-199606010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Range of Motion: Reliability and Validity of the Inclinometer Technique in the Clinical Measurement of Trunk Flexibility

Abstract: The noninvasive inclinometer technique proved to be highly reliable and valid, but the measurement technique for extension needs further refinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(141 citation statements)
references
References 20 publications
6
120
0
9
Order By: Relevance
“…For the examination of spinal mobility and back surface reconstruction by means of inclinometers, there exist satisfying reliability studies [11][12][13][14]. But for raster stereography, there is still a lack of reliability studies that are covering all parameters offered for a three-dimensional spinal form analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For the examination of spinal mobility and back surface reconstruction by means of inclinometers, there exist satisfying reliability studies [11][12][13][14]. But for raster stereography, there is still a lack of reliability studies that are covering all parameters offered for a three-dimensional spinal form analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of hip and lumbar motion has been found to have good to poor intraexaminer reliability. 35,38,45,72 Strength Testing Manual muscle testing to assess hip muscle strength was performed and graded using a 5-point scale. 34 Although all athletes exhibited at least a 4/5 hip strength rating in all muscle groups, there were subtle differences between the athletes' right and left sides.…”
mentioning
confidence: 99%
“…Numerous authors have shown high reliability and usefulness of this method for clinical examinations, e.g. Czaprowski [16], Saur et al [25], Kużdżał et al [5] and Walicka-Cupryś et al [23]. The other device used in the present study for assessing body posture is a system whose operation is based on photogrammetric method taking advantage of Moiré phenomenon.…”
Section: Discussionmentioning
confidence: 91%
“…The results reported by various researchers are difficult to compare due to the fact that different methods and measuring tools are applied; therefore, it is necessary to continue studies designed to compare results obtained with specific methods. Among the specialist publications we can encounter articles discussing concurrent validity of various techniques designed for assessing body posture [12,[23][24][25]], yet no research has previously been reported to compare the methods based on photogrammetry and gravitational inclinometer, which has been done in the present study. The two methods were used in assessing the same subjects, which made it possible to verify the assumption regarding the concurrent validity of these measurements.…”
Section: Discussionmentioning
confidence: 99%